DETERMINATION OF ROOT SENSITIVITY FUNCTION IN RESPECT OF CONTROL SYSTEM - A. A. Nesenchuk (Наука и техника)
An algorithm for determination of root sensitivity  function in the dynamic system to any change of its parameter is considered in the paper. Formulae for calculating a module and an argument of the vector root sensitivity function on the basis of analytical root locus equations and the Cauchy – Riemann conditions have been developed in the paper. The root sensitivity is determined in the given points of the system root locus in accordance with the developed algorithm.